Morphology of the Left Atrial Appendage: Prevalence and Gender Difference in a Kenyan Population - Mumin, A.; Olabu, B.; Kaisha, W.; Saidi, H.; Ogeng'o, J. (Journal of Morphological Sciences, 2018)
Introduction The left atrial appendage is the site of origin of thrombi in 90% of cardioembolic stroke. Although literature reports a higher risk of cardioembolic stroke among blacks and females, it is unclear whether this is due to preponderance of specific left atrial appendage morphologies in these groups since there is paucity of data. This study describes the left atrial appendage morphology in a Black Kenyan population and assesses for existence of gender differences.Materials and Methods Ninety one (91) human hearts (50 male and 41 female) were obtained from autopsy specimens after ethical approval. The morphological types of the left atrial appendage were determined and classified as cauliflower, Windsock, Chickenwing and cactus. Data were analyzed using Statistical Package for Social Sciences. The frequencies of the morphological types was determined and Chi square applied to check for gender differences. A p-value of < 0.05 was considered statistically significant at 95% confidence interval.Results and Conclusion There were 27 cauliflower (29.7%), 26 Windsock (28.6%), 25 Chickenwing (27.4%) and 9 cactus (14.3%) morphological types of left atrial appendage. Cauliflower and cactus types were more prevalent in males, while Windsock and Chickenwing types were more prevalent in females (p = 0.537). There are no statistically significant gender differences in the left atrial appendage morphology types in this sample black Kenyan population. The higher frequency of both the risky cauliflower and the protective Chickenwing morphologies warrants assessment of left atrial appendage morphological types in management of high risk cardioembolic stroke patients in this setting.
Keywords: left atrial appendage; gender; blacks